Epidermal growth factor receptor controls sex differences in lung type 2 responses to inhaled allergen. - Stölting,H; Raftery,AL; Walker,SA; Rutherford,EN; Gore,ML; Huang,Y; Puttur,F; Yates,L; Saglani,S; Lloyd,CM (Sci Immunol, 2026)
Hormonal disruptions are associated with poor asthma control in females, yet how these phenomena are linked remains unknown. Here, we investigated distinct allergen-induced immune responses between the sexes during maturation. By 6 weeks of life, female mice exposed to the aeroallergen house dust mite (HDM) from postnatal day 7 exhibited stronger type 2 (T2) immune responses and higher lung interleukin-33 (IL-33) than males. IL-33 administration to HDM-sensitized males was sufficient to augment T2 immunity and up-regulated epidermal growth factor receptor (EGFR) on T helper 2 (TH2) cells. EGFR inhibition abrogated T2 cytokine production in vitro. In vivo, EGFR inhibition reduced T2 immunity in females only, thereby abolishing any sex differences. 17β-estradiol (E2) heightened lung Il33 expression and T2 responses of HDM-sensitized males, akin to levels in females. EGFR's ability to drive sex differences in lung T2 responses downstream of E2 and IL-33 may link hormonal disruptions to poor asthma control.